2009
DOI: 10.1007/s12520-009-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chemical degradation compared to natural diagenetic alteration of collagen: implications for collagen quality indicators for stable isotope analysis

Abstract: Stable isotopic ratios from archaeological bone collagen are valid palaeodietary indicators, but depend on sufficiently well preserved molecules and several collagen quality criteria have to be fulfilled (mostly collagen wt%, C%; N%, C/N molar ratio). For a reassessment of these quality criteria, and a better understanding of the chemical degradation of bone collagen, experimentally degraded modern bones and 54 archaeological human bones were investigated. In the course of the experimental degradation, alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 41 publications
1
51
1
2
Order By: Relevance
“…De Niro and Weiner, 1988;Nicholson, 1998). In experimentally degraded mammalian bone, Harbeck et al (2006) and Harbeck and Grupe (2009) found the stable isotopic ratios in the extractable gelatine unaltered although the molar C/N ratios even slightly exceeded 4.0 (4.17). Therefore, the C/N ratio is not necessarily Table 5.…”
Section: Collagen Preservationmentioning
confidence: 98%
“…De Niro and Weiner, 1988;Nicholson, 1998). In experimentally degraded mammalian bone, Harbeck et al (2006) and Harbeck and Grupe (2009) found the stable isotopic ratios in the extractable gelatine unaltered although the molar C/N ratios even slightly exceeded 4.0 (4.17). Therefore, the C/N ratio is not necessarily Table 5.…”
Section: Collagen Preservationmentioning
confidence: 98%
“…To date, a number of studies have attempted to define and refine such criteria (Ambrose, 1990;DeNiro, 1985;DeNiro and Weiner, 1988;Dobberstein et al, 2009;Grupe and Turban-Just, 1998;Grupe et al, 2000;Harbeck and Grupe, 2009;Schoeninger et al, 1989;Tuross et al, 1988Tuross et al, , 1989van Klinken, 1999), but all have focused exclusively on mammalian bone. One notable exception is the work of Nehlich and Richards (2009), who suggested that because of differences in the amino acid composition of collagen, the quality criteria for sulfur isotopic analysis (C:S ratio) should be different for fish and mammalian bone.…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem diagenesis, contamination, or addition of laboratory chemicals and consolidants might alter the isotopes from their original state, thus invalidating interpretations based on these values. While well-established methods exist to monitor postmortem diagensis and contamination of buried bones (DeNiro, 1985;Tuross et al, 1989;Ambrose, 1990;Ayliffe et al, 1994;Hedges et al, 1995;Person et al, 1995;Iacumin et al, 1996;Koch et al, 1997;Lecuyer at al., 1999;van Klinken, 1999;McNulty et al, 2002;Harbeck et al, 2009), the effects of solvents and consolidants on isotope values is less wellunderstood.…”
Section: N and Dmentioning
confidence: 99%